Sampah dan Degradasi Lingkungan Sungai di Permukiman Kumuh Perkotaan - Wahyu Saputra; Muhammad Qobul Ridho Rhamadan (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2026)
Waste problems in urban slum settlements located along riverbanks have become one of the main causes of river environmental degradation. High population density, poor sanitation conditions, limited waste management facilities, and low public awareness of environmental cleanliness have contributed to increasing river water pollution and the decline of urban ecosystem quality. This study aims to analyze the relationship between waste problems and river environmental degradation in urban slum areas through a literature review approach. The research method was conducted by reviewing various scientific journals, books, research reports, and policy documents related to waste management, river pollution, slum settlements, and urban environments. The findings indicate that the direct disposal of domestic waste into rivers remains a common practice in slum settlements due to inadequate waste management services and the socio-economic conditions of the community. These conditions have resulted in declining water quality, sedimentation, river flow blockages, increased flood risks, and the emergence of various environmental-based diseases. In addition, weak supervision and poor implementation of environmental policies have further exacerbated river degradation in urban areas. This study emphasizes that addressing waste problems in urban slum settlements requires a comprehensive approach through improving waste management infrastructure, environmental education, community empowerment, and strengthening policies and collaboration among stakeholders to support the sustainability of urban river environments.